Philosophical Transcendentalism of Sharia Economic Law - Mugni Muhit; Jajang Herawan; Hasan Bisri; Ija Suntana (al-Afkar, Journal For Islamic Studies, 2023)
The transcendentality of philosophy as a radical and comprehensive way of thinking, namely exploring something deeply through the basics of ontological, epistemological, and axiological studies. Islamic legal philosophy is the main law that regulates economic, political, cultural and other social issues. Sharia economic law philosophy is essentially a scientific building on Islamic economic concepts in a comprehensive manner (al-'ilmu al-iqtishādi fi al-Islām). And scholarship that studies sharia laws that apply in society (an-nizhām al-iqtishādi fi al-Islām). The basic principles of sharia economic law include: divinity (Ilahiyah), justice (al-'Ada), trust (al-amanah), freedom (al-hurriyah), permissibility (Al-Ibahah), convenience (Al-Taisir), certainty law (al-yaqin), expediency and benefit (al-manafi wal mashalih). The essence of justice is a balance above moral values. The discovery of the ideal value of justice, then the balance of the interests of mankind both legal certainty, welfare, happiness, education can be achieved. The nature of the maker of sharia is understood in the context of God's absolute power and will, namely to realize the goodness of life in the hereafter, based on the interests of dhahuriyyat, hajiyyat and tahsiniyat. The factors causing the tendency towards sharia economics include: financial literacy, trust, location selection, profit sharing and perceptions of profit sharing, as well as implementative awareness of faith and piety.